Hubungan Antara Pengetahuan Dan Sikap Ibu Tentang Gizi Dengan Status Gizi Pada Balita Di Posyandu Mangkualam Puskesmas Cimanggu Kabupaten Pandeglang Banten : The Relationship Between Knowledge and Attitudes of Mothers About Nutrition with Nutritional Status in Toddlers at Posyandu Mangkualam Cimanggu Health Center, Pandeglang Regency Banten - Sunayah, Uyung; Usman, Andi Mayasari (Dohara POAJ, 2023)
Introduction: Toddlers are the age group that suffers the most from malnutrition and the number in the population is quite large. In 2021 Pandeglang Regency, the toddlers who were weighed reached 59,4%, found 9.3% of toddlers with malnutrition. Several factors influence the nutritional status of toddlers including knowledge and attitude of the mother. Methods: This research is a quantitative analytic study using a cross-sectional approach. The sample was mothers under five who were at the Posyandu Mangkualam Health Center Cimanggu, Pandeglang Regency, Banten in the October-December 2022 period as many as 56 respondents using the total sampling technique. The variables in this study are the nutritional status of toddlers and the knowledge, and attitudes of mothers. Bivariate analysis using Spearman rank. Results: Based on the results of a study of 56 respondents with toddlers; 82,1% had good nutritional status 41,1% had good knowledge; and 76,8% positive attitude. There is a significant relationship between the mother's knowledge (p = 0,000) and the mother's attitude (p = 0,000); with the nutritional status of toddlers. Discussion: There is a significant relationship between the knowledge and attitudes of mothers with the nutritional status of toddlers. It is hoped that mothers under five can increase their knowledge about good food intake with a balanced nutritional menu so that they can improve and maintain the nutritional status of their children under five.